Qualificação profissional stricto sensu dos técnicos-administrativos da Universidade Federal da Paraíba - Lima, Ligya Silva (2021)
The people management area has become strategic due to the changes that have occurred in organizations in general. In the public sector we highlight the institutionalization of the National Policy for Personnel Development (PNDP) and Career Plan of Technical administrative (PPCTAE), which integrate the qualification at the professional master's level, contributing to the personal and professional development of the civil servant. In this sense, the present work had as a general objective to analyze the effects of stricto sensu qualification (professional Master) in personal and professional life of technical-administrative servers of UFPB and by specific objectives to characterize the management policy at UFPB concerning the training and professional qualification; identify the profile of technical-administrative servers who completed the professional master’s degree; identify the benefits that professional Master provide to the professional daily lives of servants; indicate the possible limits of these courses in the qualification process of civil servants; propose suggestions for improvements in the stricto sensu qualification of servants. The research subjects were forty-seven public servants who had already completed the professional master's degree at UFPB. In methodological terms, the study adopted a qualitative approach of exploratory and descriptive nature. For its development were carried out bibliographic and documentary research in addition to the application of questionnaires to participants. The data analysis was performed through content analysis and allowed to know the profile of qualified servants, as well as to identify the limitations found in the qualification process, which are mainly related to the lack of time to reconcile work with study. As effects on personal and professional life of servers, were identified aspects related to increased self-esteem, expansion of knowledge, personal fulfillment, growth prospects, social recognition, among others. At last, the obtained results collaborate for the improvement of the institutional qualification policies, considering the quality of the services offered to the society.